2020
DOI: 10.1016/j.jaad.2019.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctivitis in patients with atopic dermatitis treated with dupilumab is associated with higher baseline serum levels of immunoglobulin E and thymus and activation-regulated chemokine but not clinical severity in a real-world setting

Abstract: To determine CAPB frequency in personal care products branded for children, we queried the online databases of the top 6 retailers by 2018 sales for ''baby shampoo'' and ''baby soap,'' excluding retailers that do not sell individually packaged personal care products. 5 We ordered products by ''best selling'' except where there was a dedicated ''best sellers'' page (Amazon.com), where the most representative sorting option was ''most viewed'' (CVS. com), or where there was no best-selling filter and thus the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 5 publications
0
34
1
1
Order By: Relevance
“…In the analysis of adults in dupilumab clinical trials, prior history of conjunctivitis, baseline AD severity, and elevation of circulating levels of certain biomarkers (thymus and activation-regulated chemokine [TARC, CCL17], IgE, and blood eosinophils) were associated with risk of conjunctivitis in patients in the AD trials [26]. Retrospective studies of dupilumab-treated patients with AD in clinical practice also showed significant positive associations of certain biomarkers (TARC, IgE) and prior history of ocular disorders, with an increased risk of conjunctivitis [41,42]. However, the number of conjunctivitis events among adolescent patients in the present analysis was too small to evaluate the relationships between baseline characteristics and the incidence of conjunctivitis.…”
Section: Discussionmentioning
confidence: 96%
“…In the analysis of adults in dupilumab clinical trials, prior history of conjunctivitis, baseline AD severity, and elevation of circulating levels of certain biomarkers (thymus and activation-regulated chemokine [TARC, CCL17], IgE, and blood eosinophils) were associated with risk of conjunctivitis in patients in the AD trials [26]. Retrospective studies of dupilumab-treated patients with AD in clinical practice also showed significant positive associations of certain biomarkers (TARC, IgE) and prior history of ocular disorders, with an increased risk of conjunctivitis [41,42]. However, the number of conjunctivitis events among adolescent patients in the present analysis was too small to evaluate the relationships between baseline characteristics and the incidence of conjunctivitis.…”
Section: Discussionmentioning
confidence: 96%
“…Although the data from the clinical trials could not identify risk factors specific for dupilumab-associated conjunctivitis, the real-world data suggest possible risk factors. Uchida et al reported that dupilumab-associated conjunctivitis was associated with higher baseline serum levels of IgE and TARC but not with the clinical severity of AD and that a history of conjunctivitis and eosinophils showed its tendency (Uchida et al, 2020). Nahum et al (Nahum et al, 2020) and Nettis et al (Nettis et al, 2020a) reported that the main predictor for the development of dupilumab-associated conjunctivitis was a history of conjunctivitis.…”
Section: -1-3 Risk Factors For Dupilumab-associated Conjunctivitismentioning
confidence: 99%
“…[15][16][17] Recently, accumulating evidence has revealed that dupilumab is effective for AD and it shows tolerable safety in real-world data, although the prevalence of conjunctivitis was slightly higher in the real world than in clinical trials. [18][19][20][21] Dupilumab is effective for most AD patients; however, the extent of its effectiveness varies in individual patients. It would be helpful in practice if there are predictive parameters reflecting later effectiveness of dupilumab.…”
Section: Introductionmentioning
confidence: 99%